The Ottomans and the Mamluks imperial diplomacy and warfare in the Islamic world - Muslu, Cihan Yuksel (I. B. Tauris, 2017)
Cihan Yuksel Muslu traces the intertwined stories of these two dominant Sunni Muslim empires of the early modern world, setting out to question the view that Muslim rulers were historically concerned above all with the idea of Jihad against non-Muslim entities.